Membranas de matriz contendo os MOFs UiO-66 (Zr), MIL-101 (Cr) e MOF-177 (Zn) para fracionamento do ar atmosférico - Rodrigues, Maíra Andrade (2019)
The intrinsic characteristics of energy consumption of the main technologies for O2/N2 fractionation encourage the development of more sustainable energy processes, such as separation with membranes. Mixed matrix membranes (MMM) arise with significant potential for this application. The use of MOFs in synthesis of composite membranes, besides promoting selectivity increasing to the interest gas according to the metal in the structure, enables to supplant the most cited limitation on the use of inorganic particles in the literature, which is the poor particle-polymer compatibility. In this context, UiO-66 (Zr), MIL-101 (Cr) and MOF-177 were chosen due to references in previous works on O2 adsorption with these MOFs. The most promising performance was obtained with the polyurethane membrane containing 28 wt.% of UiO-66 (Zr), with increase in ideal selectivity from 4.1 to 8.1 relative to the polymer and permeability equal to 2.7 Barrer. Considering the similar performance obtained with pure gases and gas mixtures, the oxygen concentration in the permeate is higher than that reported for commercial membranes and permeability compatible with that of some materials. The relevance of evaluating alternatives to mitigation of the greenhouse effect through CO2 capture led to the evaluation of CO2/N2 separation. The CO2/N2 selectivity determined with the gas mixture resulted in permeate with CO2 concentration equal to 86% v/v.